Andrew's loose tooth - Munsch, Robert N., 1945-; Martchenko, Michael (New York : Scholastic, 1998)
Andrew's tooth is loose and no one can help him remove it, not even the Tooth Fairy.
"Cartwheel books."
2.8
K-3
K-3
School Library Journal
Publisher's Weekly
Keywords: Teeth -- Fiction; Tooth Fairy -- Fiction; Teeth -- Fiction; Tooth Fairy -- Fiction